BRCA gene testing in women with high-grade serous ovarian carcinoma. (18th August 2021) - Kansu, Bengi; Gardner, Jennifer; Price-Tate, Rachel; Murch, Oliver; Murray, Alex
Abstract: The objective of this study was to compare the pick-up rate of pathogenic BRCA variants in those with a high-grade serous ovarian carcinoma (HGSOC) undergoing oncology-led testing with the traditional genetics family history-based testing model. With novel therapies, BRCA status can affect treatment. Welsh oncologists are now testing all women with HGSOC at diagnosis rather than referring to genetics, where family history is required for testing. The records of 332 women who underwent testing via oncology were analysed. The outcome measures were; percentage of women with a pathogenic BRCA variant and the difference in identification of pathogenic BRCA variants between the oncology-led and traditional genetics testing models. Of the 332 women, 25 women (7.5%) tested positive for a pathogenic BRCA variant. This was slightly lower than the detection rate of 9.8% for patients tested via the genetics service over the same period. Testing through genetics, using family history criteria would have identified only 19 (76%) of those with pathogenic variants in the oncology cohort. Since women with a pathogenic BRCA variant can be offered life-extending targeted treatment and a significant proportion of these women would be missed if testing was offered based on family history criteria alone, universal BRCA testing of all women with HGSOC is justified. Impact statement: What is already known on this subject? It is well established that individuals with a strong family history of breast and ovarian cancer are more likely to carry a pathogenic BRCA gene variant. With the use of tools such as the Manchester scoring system women are often invited for testing through clinical genetics services. Until recently there was no clinical impact for those already diagnosed with ovarian cancer. What do the results of this study add? Our study has shown that the diagnosis of high grade serious ovarian carcinoma alone without the need for any family history leads to a similar rate of detection of pathogenic BRCA variants as traditional methods. With the advent of targeted treatments such as olaparib, women with a pathogenic BRCA variant can access different life extending treatment options. With comparable pick-up rates to traditional family history based scoring systems, oncologists can now arrange BRCA gene testing directly. What are the implications of these findings for clinical practice and/or further research? Our study shows universal genetic testing of those with high-grade serious ovarian carcinoma by oncologists allows more women to access life extending treatment in a shorter timeframe compared to the traditional testing model used by clinical genetics services. We hope that other centres, both in the UK and beyond, will adopt this approach.